T2 mapping of the sacroiliac joints in patients with axial spondyloarthritis. Issue 131 (October 2020) - Albano, Domenico; Bignone, Rodolfo; Chianca, Vito; Cuocolo, Renato; Messina, Carmelo; Sconfienza, Luca Maria; Ciccia, Francesco; Brunetti, Arturo; Midiri, Massimo; Galia, Massimo
Highlights: SpA patients had higher T2 values than controls (59.2 ± 2.9 ms vs 44.1 ± 6.6 ms, p < .001). A T2 value of 52.37 ms allows to differentiate patients from controls (AUC 0.995). No association/correlation was found between T2 values and clinical data. Patients showed higher iliac than sacral T2 values (62.8 ± 9.8 vs 56.4 ± 11.3 ms, p < .001). Abstract: Purpose: To test whether T2 mapping of the sacro-iliac joints (SIJs) might help identifying patients with spondyloarthritis. Method: This study included 20 biologic-naive patients with axial spondyloarthritis (10 females; mean age: 38 ± 9years; range, 19–47) and 27 controls (16 males; mean age = 39 ± 13years; range = 28–71) who prospectively underwent SIJs MRI at 1.5 T, including a multislice multiecho spin-echo sequence. Standard MRIs were reviewed to assess the SIJs according to the Assessment of SpondyloArthritis International Society (ASAS) criteria and SPondyloArthritis Research Consortium of Canada (SPARCC) MRI index. T2 maps obtained from multiecho sequences were used to draw regions of interests in the cartilaginous part of the SIJs. Disease activity was assessed using BASDAI questionnaire. Bland-Altman method, ROC curve analysis, Chi square, Mann-Whitney U, Pearson's and Spearman's correlation coefficient were used for data analysis. Results: According to ASAS criteria, MRI was positive for sacroiliitis in 5/20 patients (25 %). Inter-observer reproducibility of T2 values was 87 % (coefficient of repeatability = 7.0; bias = 0.49; p < .001). Mean T2 values of patients (58.5 ± 4.4 ms, range: 52.6–68.2 ms) were significantly higher (p < .001) than those of controls (44.1 ± 6.6 ms, range: 33.6–67.2 ms). A T2 value of 52.51 ms yielded 100 % sensitivity and 91.7 % specificity to differentiate patients from controls. No statistically significant association/correlation was found between T2 values and BASDAI (r=˗.026, p = .827), disease duration (r = .024, p = .871), SPARCC (r=-.004, p = .981), ASAS criteria (p = .476), HLA-B27-positivity (p = .139), age (r=-.2.53, p = .891), and gender (p = .404). Conclusions: T2 relaxation times of the SIJs were significantly higher in patients than in healthy controls, making this tool potentially helpful to early identify patients with spondyloarthritis.